Isoprenaline and salbutamol inhibit pyroptosis and promote mitochondrial biogenesis in arthritic chondrocytes by downregulating β-arrestin and GRK2 - Ajmal, Iqra; Farooq, Muhammad Asad; Abbas, Syed Qamar; Shah, Jaffer; Majid, Muhammad; Jiang, Wenzheng (Frontiers in Pharmacology, 2022)
Rheumatoid arthritis and osteoarthritis overlap many molecular mechanisms of cartilage destruction. Wear and tear in cartilage is chondrocyte-mediated, where chondrocytes act both as effector and target cells. In current study, role of β2-AR was studied in chondrocytes both in-vitro and in-vivo. High grade inflammation in in-vitro and in-vivo disease models led to decline in anti-inflammatory β2-AR signaling and use of β2-AR agonist attenuated arthritis symptoms. Detailed analysis in chondrocytes revealed that Isoprenaline (ISO) and salbutamol (SBT) increased cell viability, relative Bcl-2 expression and the decreased expression of TNF-α, IL-6 and IL-8 in arthritic chondrocytes was detected by qPCR and ELISA, respectively. SBT preserved physiological concentration of antioxidant enzymes (CAT, POD, SOD and GSH) in cartilage homogenates and ISO inhibited IL-1β-mediated genotoxicity in arthritic chondrocytes. Moreover, β2-AR agonist increased mitochondrial biogenesis and proteoglycan biosynthesis by upregulating the gene expression of PGC1-α, NRF2 and COL2A1, Acan, respectively. ISO and SBT inhibited extracellular matrix (ECM) degradation by downregulating the gene expression of MMP1, MMP3, MMP9 and ADAMTS5 in in-vitro and in-vivo study. In mechanism, β2-AR agonists decreased β-arrestin and GKR2 pathway, and as a result mice receiving SBT did not exhibit severe disease. Hence our data suggest β2-AR agonist administered at disease onset can inhibit receptor internalization by downregulating the expression of β-arrestin and GRK2 in chondrocytes.